1989
DOI: 10.1177/0049124189018002003
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Bootstrap Methods

Abstract: Bootstrap methods are a collection of sample re-use techniques designed to estimate standard errors and confidence intervals. Making use of numerous samples drawn from the initial observations, these techniques require fewer assumptions and offer greater accuracy and insight than do standard methods in many problems. After presenting the underlying concepts, this introduction focuses on applications in regression analysis. These applications contrast two forms of bootstrap resampling in regression, illustratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
182
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(184 citation statements)
references
References 35 publications
1
182
0
1
Order By: Relevance
“…The null hypothesis of no conditional indirect effect can be rejected if the CI does not contain 0. As MacKinnon et al (2004) show in the context of simple mediator models with no moderation, the application of a bias correction to a percentile CI can improve its accuracy (for computational details, see Efron, 1987;Efron & Tibshirani, 1998;Lunneborg, 2000;Preacher & Hayes, 2006;Stine, 1989). Later we present and discuss an SPSS macro that can be used to obtain bootstrapped confidence intervals (percentile, biascorrected, and bias-corrected and accelerated) for all of the conditional indirect effects discussed in this article.…”
Section: Using Bootstrapping To Assess Moderated Mediationmentioning
confidence: 98%
See 1 more Smart Citation
“…The null hypothesis of no conditional indirect effect can be rejected if the CI does not contain 0. As MacKinnon et al (2004) show in the context of simple mediator models with no moderation, the application of a bias correction to a percentile CI can improve its accuracy (for computational details, see Efron, 1987;Efron & Tibshirani, 1998;Lunneborg, 2000;Preacher & Hayes, 2006;Stine, 1989). Later we present and discuss an SPSS macro that can be used to obtain bootstrapped confidence intervals (percentile, biascorrected, and bias-corrected and accelerated) for all of the conditional indirect effects discussed in this article.…”
Section: Using Bootstrapping To Assess Moderated Mediationmentioning
confidence: 98%
“…MacKinnon et al (2004) showed that such corrections can improve CIs and inferences when used in the context of simple mediation models. For the complex computational details of these corrections to percentile CIs, see Efron (1987), Efron and Tibshirani (1998), Lunneborg (2000), Preacher and Hayes (2006), or Stine (1989).…”
Section: Bootstrappingmentioning
confidence: 99%
“…The idea behind bootstrapping (the "bootstrap principle") is that the observed distribution of the 6*'s approximates the true distribution of Ö . Thus, this distribution of the 6°'s can be used to gain insight about the true behavior of the estimate (See Stine (1989) for a brief discussion, including the choice of resampling from residuals or from the actual data). Faraway (1990) uses bootstrapping as a method of choosing the bandwidth in kemel regression.…”
Section: Bootstrappingmentioning
confidence: 99%
“…Where data on an individual were missing, that person was excluded from analysis of that variable. As there is evidence of geographical clustering of ALL (Cuzick and Hills, 1991), confidence intervals (CIs) in the final model were estimated by bootstrapping (Stine, 1990). As the residual deviance may not be distributed as χ 2 , especially in situations such as the present, where the event data are sparse, the goodness-of-fit of the final model was checked by simulation (Bithell et al, 1995).…”
mentioning
confidence: 99%